2021
DOI: 10.1021/acsomega.1c00680
|View full text |Cite
|
Sign up to set email alerts
|

Pentameric Thiophene as a Probe to Monitor EGCG’s Remodeling Activity of Mature Amyloid Fibrils: Overcoming Signal Artifacts of Thioflavin T

Abstract: Thioflavin T fluorescence is a gold standard probe for the detection of amyloid fibrils. Herein, we showed that mature amyloid fibrils incubated with polyphenol epigallocatechin gallate (EGCG) present a fast reduction of the thioflavin T fluorescence, which is not related to remodeling activity. We propose the use of the pentameric thiophene fluorescence for monitoring the polyphenol remodeling activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Protein aggregates composed of fibrils having an extensive cross β‐pleated sheet structure are the common pathological hallmark of numerous neurodegenerative diseases, for example Alzheimer's disease (AD), and several fluorescent molecular scaffolds, such as Congo red and thioflavins, targeting these pathological entities have been developed [1–11] . Lately, thiophene‐based ligands, such as luminescent conjugated oligothiophenes (LCOs) and bi‐thiophene‐vinyl‐benzothiazoles (bTVBTs), have been applied for fluorescence imaging of protein deposits, and spectral assignment of distinct protein aggregates can be obtained by individual LCOs or combinations of ligands [12–28] . In tissue sections with AD pathology, the two pathological hallmarks, amyloid‐β (Aβ) aggregates and tau deposits, can be distinguished by anionic LCOs with a distinct chemical composition, [12–14,16] or by thiophene‐based ligands targeting specific aggregated species [17,20,27] .…”
Section: Introductionmentioning
confidence: 99%
“…Protein aggregates composed of fibrils having an extensive cross β‐pleated sheet structure are the common pathological hallmark of numerous neurodegenerative diseases, for example Alzheimer's disease (AD), and several fluorescent molecular scaffolds, such as Congo red and thioflavins, targeting these pathological entities have been developed [1–11] . Lately, thiophene‐based ligands, such as luminescent conjugated oligothiophenes (LCOs) and bi‐thiophene‐vinyl‐benzothiazoles (bTVBTs), have been applied for fluorescence imaging of protein deposits, and spectral assignment of distinct protein aggregates can be obtained by individual LCOs or combinations of ligands [12–28] . In tissue sections with AD pathology, the two pathological hallmarks, amyloid‐β (Aβ) aggregates and tau deposits, can be distinguished by anionic LCOs with a distinct chemical composition, [12–14,16] or by thiophene‐based ligands targeting specific aggregated species [17,20,27] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the conditions used during the tests, such as the types of plaques or pH of the solutions, alter the results of the remodeling of fibrils. It has been shown that, although EGCG promotes fibril remodeling, ThT may not be the best probe to assess the occurrence of this process ( Kelley et al, 2021 ). Immediately after incubating the fibril with EGCG, a reduction in ThT fluorescence was observed, but this did not represent remodeling and when the washing protocol was applied, the free EGCG was removed and ThT levels were restored to a level similar to that observed prior to treatment ( Kelley et al, 2021 ).…”
Section: History Of the Inhibitory Effects Of Epigallocatechin-gallate In Protein Aggregation And Its Use In Neurodegenerative Amyloid DImentioning
confidence: 99%
“…It has been shown that, although EGCG promotes fibril remodeling, ThT may not be the best probe to assess the occurrence of this process ( Kelley et al, 2021 ). Immediately after incubating the fibril with EGCG, a reduction in ThT fluorescence was observed, but this did not represent remodeling and when the washing protocol was applied, the free EGCG was removed and ThT levels were restored to a level similar to that observed prior to treatment ( Kelley et al, 2021 ). Thus, the authors suggested the use of pentameric thiophene as an alternative to the use of ThT in addition to the application of complementary techniques and centrifugation/washing protocols to avoid unspecific results ( Kelley et al, 2021 ).…”
Section: History Of the Inhibitory Effects Of Epigallocatechin-gallate In Protein Aggregation And Its Use In Neurodegenerative Amyloid DImentioning
confidence: 99%
“…In fact, although ThT is a gold standard probe to detect amyloid fibrils in vitro, it has been recommended caution to test polyphenols using the ThT binding assay since some critical limitations have been reported such as background signal and competitive binding with the extrinsic probe. This method needs to be validated by other techniques to confirm that the significant decrease in ThT fluorescence observed in the presence of the evaluated compound is related to an inhibitory effect on amyloid fibrillation or rather by compound displacement by ThT [237][238][239][240].…”
Section: Egcg Targeting Misfolded Aggregates In Ad and Pdmentioning
confidence: 99%
“…It should be mentioned that the reduction in ThT emission in the presence of EGCG might result from the competition of this compound with ThT for amyloid fibrils binding sites [237,238]. Recently, pentameric thiophene fluorescence was proposed as an alternative probe to monitor the aggregation kinetics in the presence of EGCG [240]. According to the study by Yang et al, it is pertinent to consider that EGCG induces two types of αsyn oligomers.…”
Section: Egcg Targeting Misfolded Aggregates In Ad and Pdmentioning
confidence: 99%